STUDY OF THE USE OF RAW MATERIALS COCONUT COIR AS ISOLATOR IN MAKING BOXES COOLING FISH (COOL BOX) - Pahlevi, M.; Syofyan, Irwandy; Sari, T. Ersti Yulika (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research was conducted on 3 to 10 December 2014 at Fishing Gear Laboratory Department of utilization aquatic resources. The purpose of the study was to utilize the coconut coir as raw material in the manufacture of insolators with a predetermined ratio to be obtained best composition. By using experimental method carried out. Tests on three cool box, coconut coir mixed with tapioca and data where analyzed descriptively. The results showed that the utilization of coconut coir as an insulating material can be used with improvements and modification in order to complete with factory made. The best result of the there treadment based on the length of time when the ice does not melt is 100 %.Keywords: Cooler Box Fish (coolbox).Insulator (insulation). Temperature